The problem of the transition from oral communications to written ones: based on the Ancient Greek literature - E. A. Pleshkevich (Библиосфера, 2019)
The article is devoted to the problem of transition in Ancient Greece from oral culture to written one. Most foreign and domestic researchers associate the duration and instability of this transition with 1) peculiarities of organizing the political power, 2) the anthropomorphic specifics of Greek culture. The author proposes to analyze applying oral and written communications in the key works of such ancient Greek writers as Homer (Iliad, Odyssey), Hesiod (Theogony), Aeschylus (Petitioner), Aristophanes (Birds), as well as philosophical works of Plato (Fedr).  It is established that the Ancient Greek authors, despite the possession of writing, guided in their works on oral communication and such forms of confidence in oral communication as personal testimony, religious oath, reinforcing all this belief in a possible religious punishment. As a result, the Ancient Greek authors either ignore or portray as secondary written communication in the absence of specially created institutional forms of trust. The author proposes an original hypothesis, in the context of which he explains this phenomenon by the inability of institutional forms of confidence created for oral communications to perform its function in the transition to written communications and «slows down» the transition process. The author’s hypothesis is based on the theory of documentary information, in which context the final transition to written communications was completed only after the creation of institutional forms of confidencein written communications in the form of archives and libraries.